(3QSGdI GdbSWfWjfjI GdefaPI Edi bSWfWjf eeJdc GdfUQGfjIs - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj , J (B433 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi Gdehdi GdEdg GdMGce GdefRg HGdJbOjS hGdJSHjM hTcQJ YHOg GdEeGe GdSjO GdeSjM ef GdYHO GdNGVY GdfGUM s
(3BNQgG (B:s
(3hWHY dg NGJe GdYRI hGdHbGA hCadM ef GdebGdjO hGdMeO dehdGfG GdMGce hMOg hGdTcQ deSHM GdCee hgGOjgG YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B53s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds